Assessment of Tooth Mobility in Periodontitis Patients Below the Age Of 35 Years - An Institutional Based Retrospective Study - RAJ, B. JOHN ROZAR; S, BALAJI GANESH.; M. S, NIVEDITHA. (The journal of contemporary issues in business and government, 2021)
Tooth mobility is the degree of displacement of the tooth from the socket on the application of force. It is an important clinical feature in the diagnosis of periodontal diseases. The aim of the study was to assess the tooth mobility in periodontitis patients under the age of 35 visiting a private dental institution. This was a retrospective study. Samples were collected from June 2019 to March 2020. Data of the periodontal status of patients visiting a private dental institution in the age group of 18 to 35 years were collected. Excel tabulation was done and SPSS results were obtained. In this study, it was shown that 1993 patients were diagnosed with periodontal diseases. Among those patients, 1676 patients were diagnosed with localized chronic periodontitis, 302 patients were diagnosed with generalized chronic periodontitis, 10 patients were diagnosed with localized aggressive periodontitis and 5 patients were diagnosed with generalized aggressive periodontitis. Among patients with mobility, 82% had Grade 1 mobility, 13% had Grade 2 mobility and 5% had Grade 3 mobility. From the present study, we can conclude that Grade 1 mobility was seen more in all the age groups when compared to Grade 2 and Grade 3 mobility. It was also found that Grade 1 mobility was predominantly seen in the age group of 25-30 years. The association of tooth mobility in different age groups was found to be statistically significant (p value- 0.023). Grade 1 mobility was more common in male patients. Grade 1 mobility was more common in localized chronic periodontitis patients. The association of tooth mobility with respect to different types of periodontal diseases was found to be statistically significant (p value- 0.004). Localized chronic periodontitis was seen more commonly among all age groups but predominantly in the age group of 25-30 years. The association of different types of periodontal diseases in different age groups was found to be statistically significant (p value- 0.01). Localized chronic periodontitis was seen more commonly in male patients when compared to other types of periodontal diseases. The key to successful management of periodontal disease at younger age patients lies in early diagnosis of the disease and rigorous treatment employing the different treatment modalities followed by meticulous lifelong maintenance therapy.